2013
DOI: 10.1074/jbc.m113.477943
|View full text |Cite
|
Sign up to set email alerts
|

The Allosteric Role of the AAA+ Domain of ChlD Protein from the Magnesium Chelatase of Synechocystis Species PCC 6803

Abstract: Background: Magnesium chelatase catalyzes the first essential step in chlorophyll biosynthesis.Results: Mutations in the AAA+ domain of the magnesium chelatase ChlD subunit reduce but do not abolish catalytic activity.Conclusion: ChlD is an allosteric regulator of magnesium chelatase.Significance: These observations reveal an essential role for the ChlD protein in the first committed stage in chlorophyll biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 22 publications
3
33
0
Order By: Relevance
“…9,12 In line with our previous work, no magnesium cooperativity was observed with the T. elongatus ChlD protein, even under the broader range of experimental conditions used here ( Figure S5). 12 The Synechocystis/T.…”
Section: −16supporting
confidence: 74%
See 2 more Smart Citations
“…9,12 In line with our previous work, no magnesium cooperativity was observed with the T. elongatus ChlD protein, even under the broader range of experimental conditions used here ( Figure S5). 12 The Synechocystis/T.…”
Section: −16supporting
confidence: 74%
“…12 This observation that the ChlD protein from Synechocystis is involved in magnesium cooperativity and the demonstration that the N-terminal AAA + nucleotide binding site allosterically controls chelatase activity lead to the view that the ChlD subunit acts as a regulatory hub for magnesium chelatase. 9,10 However, we do not know the basis for this control. The recent determination of the structure of the catalytic ChlH subunit 13 is an important step in understanding the structural basis for regulation and catalysis in magnesium chelatase mediated by ChlD.…”
Section: * S Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlation argues for the requirement of proximity of the GUK and its protein substrate enabling rapid control of GUN4 by phosphorylation. Although ATP hydrolysis takes place during MgCh catalysis (Jensen et al, , 1998Adams and Reid, 2013), a phosphate transfer to GUN4 by the MgCh subunits H, D, and I was not observed in vitro (Supplemental Fig. S1).…”
Section: Gun4 Is Phosphorylated By a Plastid Membrane Localized Kinasementioning
confidence: 99%
“…Bioinformatic analysis suggested that there is a weak similarity between the MIDAS extension region and the D subunit of magnesium chelatases based upon the high density of basic and hydrophobic residues just upstream of the MIDAS domain (23). Magnesium chelatases, which play an important role in chlorophyll biosynthesis by inserting Mg 2ϩ into protoporphyrin, also contain C-terminal MIDAS domains and two N-terminal AAA domains (47). In addition to magnesium chelatases and midasin, there is only one other known protein, VWA8 (only found in higher organisms; function is unknown), that contains the combination of AAA and MIDAS domains (37).…”
Section: Discussionmentioning
confidence: 99%